A case study on borders in retail spaces. (24th June 2019) - Ceylan, Salih
Abstract : Purpose: The existence of retail spaces lies far back in history. However, retail design as an academic field of work is relatively recent and available for development. The common points and differences between commercial spaces and retail spaces, as well as the relationship between private and public spaces, require academic attention from a retail perspective. The purpose of this paper is to contribute to the academic knowledge on retail design by interpreting retail spaces according to their relationship with their surroundings and their way of defining borders. Design/methodology/approach: The focal point of the paper lies on a case study based on built examples of retail spaces in Turkey. An actual perspective, along with the historical background of retail design, provides the theoretical framework of the study, as the term "border" is being interpreted according to encountered restrictions and intentions throughout the retail design process. Findings: The case study conducted in the scope of this paper has shown that borders are an important component in retail design and they are affected by various factors like the limitations of the surroundings and atmospheric tools such as colours, lighting, sound or scent. Originality/value: Although there are existing studies on retail design from various perspectives, the interpretation of retail spaces in relationship with their borders is missing in academic literature. This paper provides a definition of borders in retail design including the elements that describe them and the knowledge of borders according to different corporate tendencies.